2016
DOI: 10.3109/1354750x.2016.1171911
|View full text |Cite
|
Sign up to set email alerts
|

Soluble urokinase plasminogen activator receptor informs on the progression course after multiple injuries

Abstract: suPAR is a useful surrogate biomarker for development of MOF and severe sepsis after multiple traumas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…Another possibility is that suPAR is related to a systemic chronic inflammatory state. It is well established that chronic inflammation may be responsible for insidious tissue damage (Furman et al, 2019), and elevated suPAR is associated with multiple organ failure and sepsis (Patrani et al, 2016;Zeng et al, 2016). Therefore, high suPAR may indicate a state of chronic low-grade inflammation that predisposes a patient to kidney damage.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that suPAR is related to a systemic chronic inflammatory state. It is well established that chronic inflammation may be responsible for insidious tissue damage (Furman et al, 2019), and elevated suPAR is associated with multiple organ failure and sepsis (Patrani et al, 2016;Zeng et al, 2016). Therefore, high suPAR may indicate a state of chronic low-grade inflammation that predisposes a patient to kidney damage.…”
Section: Discussionmentioning
confidence: 99%
“…When a body suffers from a tumor, inflammation, and other pathological conditions, uPAR is upregulated and released into the blood circulation by hydrolysis of phospholipase or protease. suPAR is a soluble form of uPAR and a promising prognostic biomarker [26][27][28]. A study indicated that suPAR could predict the hospital and long-term mortalities in patients with critical illness and sepsis [29].…”
Section: Prognostic Biomarkers Of Survival Ratementioning
confidence: 99%
“…119 Απνηειεί ηνλ θαιχηεξν βηνδείθηε γηα ηελ έγθαηξε πξφγλσζε ηεο δπζκελήο πνξείαο αζζελψλ πνπ λνζειεχνληαη ζε κνλάδα εληαηηθήο ζεξαπείαο θαη έρνπλ βαζκνινγία APACHE II >17. 120 Αχμεζε ηνπ suPAR >40% ζε ζρέζε κε ηελ αξρηθή ηηκή θαηά ηελ εηζαγσγή ηνπ αζζελνχο απνηειεί δηαγλσζηηθφ θξηηήξην γηα ηε ζήςε κε εηδηθφηεηα 90%.…”
Section: ) Supar (Soluble Urokinase Plasminogen Activator Receptor)unclassified